Evaluating Treatment Outcome in an Interdisciplinary Pediatric Pain Service - Susan M Bennett; Christine T Chambers; Doria Bellows; Colleen A Court; Elizabeth Huntsman; Carolyne Montgomery; Tim F Oberlander; Michelle Sheriff; Harold Siden (Pain Research and Management)
OBJECTIVE: To provide descriptive data evaluating outcome and treatment satisfaction among former pediatric patients and their parents seen in an interdisciplinary treatment program for complex pain syndromes.